2018
DOI: 10.1136/bmjopen-2017-021468
|View full text |Cite
|
Sign up to set email alerts
|

Is elevation of N-terminal pro-B-type natriuretic peptide at discharge associated with 2-year composite endpoint of all-cause mortality and heart failure hospitalisation after transcatheter aortic valve implantation? Insights from a multicentre prospective OCEAN-TAVI registry in Japan

Abstract: ObjectivesThe aim of this study was to investigate the 2-year prognostic impact of N-terminal pro-B-type natriuretic peptide (NT-proBNP) levels at discharge following transcatheter aortic valve implantation (TAVI).DesignMulticentre prospective observational study.SettingsSeven institutions from multicentre, observational registry of symptomatic patients with severe aortic stenosis who undergo TAVI.ParticipantsWe enrolled 500 consecutive patients who underwent TAVI with measurements of NT-proBNP at discharge be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…This was confirmed in our analysis showing elevated levels of NT‐pro BNP in patients with advanced DD compared to patients with normal or less advanced DD. Previous studies have shown that elevated NT‐pro BNP levels correlate with long‐term mortality in patients with severe AS after TAVR . Our study results are in line with these observations.…”
Section: Discussionsupporting
confidence: 92%
“…This was confirmed in our analysis showing elevated levels of NT‐pro BNP in patients with advanced DD compared to patients with normal or less advanced DD. Previous studies have shown that elevated NT‐pro BNP levels correlate with long‐term mortality in patients with severe AS after TAVR . Our study results are in line with these observations.…”
Section: Discussionsupporting
confidence: 92%
“…To provide a simple, exploratory analysis, we performed survival classification and regression tree (CART) analysis using the primary end point as an outcome variable, with preprocedural musclin levels as an independent variable. 19 , 20 , 21 , 22 The purpose was to identify the cutoff value of musclin for the risk stratification of the primary end point. 23 Next, we divided the study population into 2 groups based on this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion criteria of this registry were previously reported. 6,7 All patients were treated with TAVR based on the clinical consensus of a heart team comprised of cardiac surgeons, interventional cardiologists, and anesthesiologists. Between October 2013 and May 2017, 2588 TAVR patients were registered in the OCEAN-TAVI registry.…”
Section: Study Population and Designmentioning
confidence: 99%